the problem is
(3m+2/5m)+(2m-1/2m)
please help?
i dont understand how to do these
the problem is
(3m+2/5m)+(2m-1/2m)
please help?
i dont understand how to do these
This can be explained with help from the distributive property.
a * b + a * c = a * (b + c)
3 * m + 2/5 * m
a = m
b = 3
c = 2/5
a * (b + c) => (3 +2/5) * m = 3.4 * m
That's a start. Use that method to find the other side of the expression (2*m-1/2*m) and combine the two. Good luck!
Daisy, that is expression, and you have to simplify it.
3m + 2 2m - 1
———— + ———— =
5m 2m
(m ≠ 0)
2(3m + 2) 5(2m - 1)
————— + ————— =
10m 10m
6m + 4 + 10m - 5
————————— =
10m
(16m - 1) / 10m